Pengukuran Perangkat Lunak Menggunakan Function Point Analysis – Studi Kasus Software Akuntansi “Beecloud” - Denny Agung Situmeang (Teknik: Jurnal Ilmu Teknik dan Informatika, 2023)
Accounting software is a must have for small and large companies. In carrying out its business the company uses special accounting software. To find out how complex the software used , it is necessary to have software measurements . Measurements use the Function Point Analysis method where measurements are measured based on their functionality. There are 3 factors used as measurement tools, namely Crude Function Point (CFP), Relative Complexity Adjustment Factor (RCAF), and Function Point (FP). Based on the results of calculations using 3 methods, the Crude Function Point (CFP) is 11548, the Relative Complexity Adjustment Factor (RCAF) is 64, the Function Point (FP) is 15330.4. From the results obtained from calculations using the Function Point Analysis method, it can be seen that the Beecloud web-based accounting software is very complex.